Intercultural Communication Competence Model in English Speaking Classroom - Harni Jusuf; Enni Akhmad Daud; Sukmawati Basri Tawe (Institut Agama Islam Negeri Imam Bonjol Padang, 2024)
This study aims to describe the application of the intercultural communication competence model in English speaking classroom. The researchers used descriptive qualitative research, in which two lecturers and eight students of English Education Department IAIN Sultan Amai Gorontalo as the participants. The data collection techniques used interviews and documentation. The data analysis technique was carried out through four stages, namely data collection, data reduction, data display and conclusions. The results showed that lecturers used American dialects, the lecturers used social media such as Instagram to introduce viral everyday English, the lecturers used personal experience and role play to make students understand about other people's cultures in English speaking classroom. and This research implied that that Intercultural Communicative Competence model provide information to lecturers how to apply that model in English Speaking Classroom.